2018
DOI: 10.1186/s13104-018-3937-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival status and predictors of mortality among children with severe acute malnutrition admitted to general hospitals of Tigray, North Ethiopia: a retrospective cohort study

Abstract: ObjectiveDespite the presence standard protocol for management of severe acute malnutrition case-fatality rates in African hospitals remain unacceptably high. The case in Ethiopia is not different from others. Therefore, this study was aimed to assess survival status and predictors of mortality among children with severe acute malnutrition admitted to stabilization centers of general hospitals in Tigray region, northern Ethiopia. A 24 months retrospective longitudinal study was conducted among 569 randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
43
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 12 publications
(13 reference statements)
14
43
6
Order By: Relevance
“…Younger children may be more vulnerable because of depressed immunity, increased risk of infection and insufficient feeding practices [10]. This finding was also supported by findings from other African studies [9,25,26]. Children with comorbidities/complication at admission were 3.25 times more likely to die than children without co-morbidities/complication in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Younger children may be more vulnerable because of depressed immunity, increased risk of infection and insufficient feeding practices [10]. This finding was also supported by findings from other African studies [9,25,26]. Children with comorbidities/complication at admission were 3.25 times more likely to die than children without co-morbidities/complication in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Children with comorbidities/complication at admission were 3.25 times more likely to die than children without co-morbidities/complication in our study. Similar results were reported in Ethiopia by Jarso et al (2015) and more recently by Guesh et al (2018) [10,26]. Complicated SAM is typically associated with an inpatient mortality risk of 12% to more than 30% in African hospitals [11,[27][28][29] A meta-analysis of inpatient treatment outcomes of SAM among under-5 children in Ethiopia concluded that comorbidities at admission were predictors of mortality [30].…”
Section: Discussionsupporting
confidence: 73%
“…The recovery rate in this study was also higher than the findings various studies performed in different locations of Ethiopia [12,14,16,17,20,21,24,26,27,30,[33][34][35][36][37][38][39][40], of which ten [12,14,16,17,20,26,27,33,36,40], five [24,30,34,35,39], two [37,38], and one [21] were from Northern, Southern, Western and Easter Ethiopia, respectively. However, it was also lower than previous studies done in Ethiopia [13,23,25,41], of which two of them were from Northern Ethiopia [23,41] and others were from Western [13] and Southern [25] Ethiopia. These discrepancies could be attributed to differences in the organizational set-up, study and sample population, socio-demographic differences of the study subjects and variation in study settings.…”
Section: Plos Onecontrasting
confidence: 69%
“…The most retrieved studies (32 studies) were from Ethiopia [4,5,17,18,, followed by Malawi (n = 6 studies) [56][57][58][59][60][61], and Nigeria (n = 3 studies) [62][63][64]. Cameroon [65,66], Kenya [67,68], Sudan [69,70], and Ghana [71,72] were represented by two studies, whereas South Africa [73], Uganda [74], Niger [75], Zambia [76], and Democratic Republic of Congo (DRC) [77] were represented by one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of these, 2.2 million were found in Sub-Saharan African countries [3]. SAM is continuing to be the major public health problem and an essential contributor to morbidity and mortality in under-five children [4,5]. In interventions taken by community health workers, a recovery rate of around 90% was estimated in a systematic review and meta-analysis done in middle-and low-income counties [6].…”
Section: Introductionmentioning
confidence: 99%